US-Guided Biopsies: Overarching Principles - Meric De Bellefon, Laurent; Lazarou, Ilias (Frontiers in Medicine, 2019)
Gathering synovial tissue from any swollen joint especially in early arthritis patients is critical for good quality research and to obtain further insight into the pathophysiology of inflammatory joint diseases. Multiplying biopsy sites is a challenge in terms of the techniques needed for each different joint but also in terms of safety and tolerability. It is important to provide the best care especially in very early arthritis patients who have only had the disease for a few months. This review discusses the minimal requirements applying to antiseptic techniques for the operator's hands, patient preparation, local anaesthesia and post-procedure care.